Generation of a Hutchinson–Gilford progeria syndrome monkey model by base editing. Issue 11 (29th July 2020) - Wang, Fang; Zhang, Weiqi; Yang, Qiaoyan; Kang, Yu; Fan, Yanling; Wei, Jingkuan; Liu, Zunpeng; Dai, Shaoxing; Li, Hao; Li, Zifan; Xu, Lizhu; Chu, Chu; et al.
Abstract: Many human genetic diseases, including Hutchinson-Gilford progeria syndrome (HGPS), are caused by single point mutations. HGPS is a rare disorder that causes premature aging and is usually caused by a de novo point mutation in the LMNA gene. Base editors (BEs) composed of a cytidine deaminase fused to CRISPR/Cas9 nickase are highly efficient at inducing C to T base conversions in a programmable manner and can be used to generate animal disease models with single amino-acid substitutions. Here, we generated the first HGPS monkey model by delivering a BE mRNA and guide RNA (gRNA) targeting the LMNA gene via microinjection into monkey zygotes. Five out of six newborn monkeys carried the mutation specifically at the target site. HGPS monkeys expressed the toxic form of lamin A, progerin, and recapitulated the typical HGPS phenotypes including growth retardation, bone alterations, and vascular abnormalities. Thus, this monkey model genetically and clinically mimics HGPS in humans, demonstrating that the BE system can efficiently and accurately generate patient-specific disease models in non-human primates.